Implementing Instruction with Metaverse: Insights from the TRINGO Concept - Hasan, Hasan; Kuswandi, Dedi; Thaariq, Zahid Zufar At (FKIP Universitas Lampung, 2023)
Implementing Instruction with Metaverse: Insights from the TRINGO Concept. Objective: The purpose of this study is to investigate the implementation of learning using the metaverse, and to link it to the TRINGO approach. Methods: Through a combined meta-synthesis and narrative approach, the results show the positive impact of the metaverse in learning. Findings: The